Comment on Effective of the q-deformed pseudoscalar magnetic field on the charge carriers in graphene [J. Math. Phys. 57, 082105 (2016)] - Obispo, Angel E.; Freitas, Gisele B.; Castro, Luis B. [UNESP] (AIP Publishing, 2019)
We point out a misleading treatment in a recent paper published in this journal [M. Eshgi and H. Mehraban, J. Math. Phys. 57, 082105 (2016)] concerning solutions for the two-dimensional Dirac-Weyl equation with a q-deformed pseudoscalar magnetic barrier. The authors misunderstood the full meaning of the potential and made erroneous calculations, and this fact jeopardizes the main results in this system.